SPECIFICS OF TEACHING SELECTIVE DISCIPLINE AT THE DEPARTMENT OF PROSTHETIC DENTISTRY FOR FOREIGN STUDENTS OF THE SECOND YEAR STUDY - Hasiuk P.А.; Demkovych, A.Ye.; Rosolovska, S.O.; Vorobec, A.B.; Radchuk, V.B.; Bedeniuk, O.A. (World of Medicine and Biology, 2018)
The article presents the specifics of introducing a new model of the educational process organizing – European Credit Transfer and Accumulation System (ECTS) into the educational process. The principal distinctive feature of this design system within the discipline “Basic manufacturing technology of dental prostheses” is structuring it into sections and introduction of credit scorings as a unit for measuring a student’s educational load. Among the disciplines studied at the Department of Prosthetic Dentistry at “I. Horbachevsky Ternopil State Medical University”, the new curriculum provides studying of selective discipline “Basic manufacturing technology of dental prostheses” for the 2nd year English-speaking students. Teaching of the discipline is carried out in English and provides lectures, seminars, individual work of students and ends with credit scorings. Knowledge and skills acquired by English-speaking foreign students in the course of the discipline “Basic manufacturing technology of dental prostheses”, aimed at the detailed study of the dental prostheses manufacture technological aspects, is a necessary component of the dentist’s professional competence.